Implementation of Patient Safety Goals (SKP) in Hospital Services: Systematic Review - Ganik Sakitri; Sunaryo Joko Waluyo (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Background: Patient safety is a primary indicator of healthcare service quality and remains a critical global priority. The World Health Organization reported approximately 134 million hospital injury cases in 2019, causing 2.6 million deaths. In Indonesia, national data recorded 4,397 patient safety incidents in 2021, with Central Java province ranking as the second highest contributor (15.9%), highlighting the urgent need for consistent safety standard enforcement. Objective: This study aims to comprehensively analyze the implementation of the six Patient Safety Goals in hospital services, identify the underlying barriers, and outline strategic factors that influence healthcare workers' compliance. Methods: A qualitative approach using a narrative literature review was conducted. Database searches were carried out via PubMed and Google Scholar for full-text articles published between 2020 and 2026. Applying the PRISMA framework, duplicates and irrelevant papers were systematically screened out, resulting in a final synthesis of 8 qualified articles for thematic evaluation. Results: The review indicated that healthcare compliance in executing safety goals ranged between 65% and 92%. Goal 5 (Infection Risk Reduction: 85%–95%) and Goal 1 (Patient Identification: 75%–88%) achieved the highest compliance rates. Conversely, Goal 2 (Effective Communication: 60%–72%) and Goal 6 (Fall Risk Reduction: 65%–78%) represented the weakest operational points. Primary operational barriers include high nursing workloads, emergency shifts, administrative rush during surgical time-outs, space limitations for separating look-alike sound-alike medications, and a lack of ongoing fall risk re-assessments. Organizational success is significantly driven by supportive leadership supervision, a well-established non-blaming culture, balanced staffing ratios, and seamless supply chains for safety logistics. Conclusion: Successful implementation of patient safety protocols requires active interprofessional collaboration and a profound transition toward a supportive safety culture. While basic procedural knowledge is widely sustained, intensive managerial interventions are critically required to optimize clinical communication workflows and maintain continuous risk re-evaluations to guarantee safe hospital care.